Modernity and capitalism in the modern technique:: Bolívar Echeverria as a technical philosopher - García Conde, Gustavo (2023)
The article deals with the reflection that Bolívar Echeverría made about modern technique, analyzing the different types of technique: magic, playful and capitalist. The subject is addressed in relation to Bolívar Echeverría's general approach to modernity and its relationship with capitalism, to explain the development of the history of technology and how it was substantially altered by capitalism. In the article, Echeverría's approach establishes dialogue mainly with Lewis Mumford, Walter Benjamin and Karl Marx. The main thesis of the work maintains that the ludic technique was the only one that could fulfill the emancipatory objectives of modernity, but that these were truncated by the capitalist use of technology.